Cognitive Impairment in Patients Requiring Mechanical Ventilation and Sedation Due to Critical Illness: A Prospective Observational Study - Anwar, Ali; Nazir, Humaira; Hassan, Aaiz; Khan, Faizan Ali; Khan, Agha Hashim Raza; Ahmad, Daler (Biological and Clinical Sciences Research Journal, 2025)
Cognitive impairment is a significant and often under-recognized consequence among critically ill patients who undergo mechanical ventilation and sedation. The depth and duration of sedation are increasingly implicated in long-term neurocognitive deficits, necessitating careful evaluation of sedation practices in intensive care units (ICUs). Objective: To assess the prevalence and progression of cognitive impairment in critically ill patients undergoing mechanical ventilation with sedation and to determine the association between sedation type, duration, and cognitive outcomes. Methods: A prospective observational study was conducted from April to September 2024 in the medical, surgical, and cardiac ICUs of a tertiary care hospital. A total of 150 adult patients (aged ≥18 years) requiring mechanical ventilation for ≥48 hours and sedated with midazolam, propofol, or dexmedetomidine were enrolled. Exclusion criteria included pre-existing cognitive or neurologic disorders. Cognitive function was assessed using the Montreal Cognitive Assessment (MoCA) and Mini-Mental State Examination (MMSE) at ICU discharge, and again at 3- and 6-month follow-up. Sedation parameters, comorbidities, and demographic data were also collected. Statistical analysis was performed using SPSS v25.0. Results: The mean patient age was 58 ± 12 years; 43.3% were male. Cognitive impairment was identified in 28% of patients at ICU discharge, declining to 20% at 3 months and 12% at 6 months. Midazolam was used in 40% of patients, propofol in 35%, and dexmedetomidine in 25%. MoCA scores were highest among patients receiving dexmedetomidine (mean: 26.5 ± 1.8), followed by propofol (24.3 ± 2.1), and lowest with midazolam (22.1 ± 2.5). A significant negative correlation was observed between sedation duration and MoCA score (r = -0.45, p < 0.001), indicating that longer sedation durations were associated with greater cognitive decline. Conclusion: Cognitive impairment is a prevalent and clinically significant complication in critically ill patients receiving sedation and mechanical ventilation. The type and duration of sedation play crucial roles in influencing cognitive outcomes. Dexmedetomidine appears to be associated with better cognitive recovery, while midazolam is linked to poorer outcomes. Strategies aimed at minimizing sedation duration and prioritizing agents with a favorable cognitive profile should be integrated into ICU sedation protocols to enhance long-term patient recovery.